A CASE REPORT ON SYSTEMIC-ONSET JUVENILE IDIOPATHIC ARTHRITIS (SOJIA) WITHOUT MULTIORGAN INVOLVEMENT - KHAN, PATHAN AMANULLA; NOUSHEEN BB, SARAH; BEGUM, ASFIYA; JABEEN, RAQSHAN; HUSSAIN, YOUSUF (Innovare Journal of Sciences, 2021)
Systemic-onset juvenile idiopathic arthritis (SoJIA) is a rare form of juvenile idiopathic arthritis (JIA) which manifests as quotidian fevers and arthritis in one or more joints. Features include characteristic salmon pink-colored rash associated with lymphadenopathy, hepatosplenomegaly, and serositis. To the best of our knowledge, this is a rare form of JIA in India and very few cases without multiorgan involvement have been published in literature. The following case reports a 12-year-old male child who presented to the hospital with a history of spiking fevers and arthritis in the knees, ankle, and hip joints. Diagnosis of SoJIA was confirmed after subsequent laboratory investigations; treatment included long-term nonsteroidal anti-inflammatory drugs, and methotrexate. However, due to increased cost of medicines and no guaranteed “cure” for the disease, the present patient switched from allopathic to homeopathic medicines. He still experiences frequent flare-ups associated with the disease, during which aceclofenac is taken for symptom relief. This case also highlights the importance of a “cure” for diseases rather than “symptom-oriented” treatment measures. When a cure is not guaranteed, patients may transition to inexpensive alternate therapies portraying limited efficacy. Further research in the field of rheumatology, specifically for rare diseases, is warranted.